The Agricultural Blogosphere: A Snapshot of New Agricultural Communicators Online - Emily Rhoades; Kelsey Hall (Journal of Applied Communications, 2007)
Political science and journalism researchers have extensively explored the characteristics of biogs and the users who produce and read them. However, blogging research has tended to focus on a few specific genres, such as politics and popular culture, and has not usually included agricultural blogging. Biogs have emerged as an alternative to traditional media sources, making it important to understand if the trend of minimal agricultural coverage continues online. It is also important to understand who serves as "reporters" of agriculture in the blogosphere. This content analysis of 52 agriculture biogs—all of which originate in North America—shows that while many characteristics of these biogs are similar to those of other genres, the age of the blogger and frequency of blogging tend to be different. While many mainstream biogs serve as personal journals offering glimpses into the author's life, agriculture biogs mainly focus on filtering news and information for readers. These biogs cover agricultural issues ranging from livestock and crops to biotechnology, biodiesel, and politics.